A Comparative Study on Math-Science and Social Students Concerning Their Passive Voice Mastery: A Comparative Study at the Second Year Students of State Senior High School 6 of Palembang - Mia Rosa Anggraini (Universitas PGRI Palembang, 2018)
Abstract: The main problem of this study was â€œIs there any significant difference in passive voice mastery between the eleventh grade students in math-science and social major of State Senior High School 6 of Palembang?â€ Thus, the main objective of this study was to find out whether or not there is significant difference in passive voice mastery between the eleventh grade students in math-science and social major. In conducting the study, the writer used causal-comparative analysis. To obtain the data, the writer used two instruments; passive voice test and questionnaire. The data of passive voice test was analyzed through Standard Deviation (SD) finding which is combined to the Degree of Freedom finding (DF), and used the T-Test formula with Separated Variance Pattern. In analyzing the questionnaire, the writer calculated the percentage of each item. Based on the analysis, the average score of passive voice test obtained by math-science students was 88.2 while social students got 80.9. Furthermore, the result of questionnaire showed that math-science students gave 75% of positive perceptions toward English class, on the other hand, social students only gave 25%. The calculation of comparative analysis showed that tobservation was lower than ttable (0.184<1.995). It indicates that Ho was accepted and Ha was rejected. In other words, there was no significant difference in passive voice mastery between the eleventh grade students in math-science and social major of State Senior High School 6 of Palembang.Â